Nevanlinna characteristics and defective values of the Weierstrass zeta function - Zaionts, Yu.; Korenkov, M. E.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We establish the Nevanlinna characteristics of the Weierstrass zeta function and show that none of the values a C is exceptional in the Nevanlinna sense for this function.